2002
DOI: 10.1128/cmr.15.4.757-770.2002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Global Climate on Infectious Disease: the Cholera Model

Abstract: Recently, the role of the environment and climate in disease dynamics has become a subject of increasing interest to microbiologists, clinicians, epidemiologists, and ecologists. Much of the interest has been stimulated by the growing problems of antibiotic resistance among pathogens, emergence and/or reemergence of infectious diseases worldwide, the potential of bioterrorism, and the debate concerning climate change. Cholera, caused by Vibrio cholerae, lends itself to analyses of the role of climate in infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
572
0
19

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 637 publications
(602 citation statements)
references
References 138 publications
(134 reference statements)
11
572
0
19
Order By: Relevance
“…To develop an early warning system for outbreaks, forecasting methods would be interesting, although a comprehensive understanding of the disease dynamics and all parameters involved is necessary. The model for environmental cholera transmission proposed in the literature 15 would be helpful.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To develop an early warning system for outbreaks, forecasting methods would be interesting, although a comprehensive understanding of the disease dynamics and all parameters involved is necessary. The model for environmental cholera transmission proposed in the literature 15 would be helpful.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this observation, theoretical models were developed that included environmental variables as causal factors for cholera re-emergence in an attempt to describe its dynamics. 15 In real-life conditions, positive correlations were shown to exist between an upsurge in the number of cholera cases during an outbreak and the increase in sea surface temperature 8 weeks earlier. 16,17 Hence, upon describing epidemiological variables of outbreaks and analysing related climate variables, mathematical models can be built providing necessary information to predict the evolution of cholera epidemics.…”
Section: Introductionmentioning
confidence: 99%
“…Qian et al (2008) found a synergistic effect of PM 10 and high temperatures on daily cardio-respiratory (Bell et al, 2007;Confalonieri et al, 2007;Dominici et al, 2006;Fiala et al, 2003;IPCC, 2007a;Katsouyanni et al, 1993;Knowlton et al, 2004;Koken et al, 2003;Mauzerall et al, 2005;Ordonez et al, 2005;Rainham and Smoyer-Tomic, 2003;Ren and Tong, 2006) ▪ The elderly and individuals with pre-existing cardio-respiratory disease may be more vulnerable to these effects Altered exposure and risk ▪ Some populations may experience increases or decreases in POP exposures and health risks depending on the region and diet of exposed individuals (Bard, 1999;Gordon, 1997;McKone et al, 1996;Watkinson et al, 2003) ▪ Pesticides may impair mechanisms of temperature regulation especially during times of thermal stress Increased susceptibility to pathogens ▪ Toxicants can suppress immune function, and climate-induced shifts in disease vector range will result in novel pathogen exposure (Abadin et al, 2007;Haines et al, 2006;Lipp et al, 2002;Nagayama et al, 2007;Patz et al, 2005;Rogers and Randolph, 2000;Smialowicz et al, 2001) ▪ Immune system impairment linked to toxicants may increase human vulnerability to climate shifts in pathogens ▪ Low-income populations, infants, children, and the chronically ill may be more susceptible exposures may sensitize individuals to allergic disease ▪ Low-income populations, infants, children, and the chronically ill may be more susceptible mortality in Wuhan, China. The PM 10 effects were strongest on extremely high temperature days (daily average temperature 33.1°C) and weakest during normal temperature days (daily average temperature 18°C).…”
Section: Air Pollutants and Cardio-respiratory Diseasementioning
confidence: 99%
“…The distribution and emergence of vector-borne diseases, such as malaria and cholera, are predicted to be dependent on temperature, humidity, and precipitation (Lipp et al, 2002;Patz et al, 1996Patz et al, , 2005Rogers and Randolph, 2000). As such, climate change is predicted to facilitate the reemergence or expansion of endemic vector-borne diseases or might promote the migration of these diseases to new regions.…”
Section: Increased Vulnerability To Disease Vectorsmentioning
confidence: 99%
“…Its natural reservoir is the aquatic environment (49,84). Cholera pandemics are caused by specific serogroups of V. cholerae that are pathogenic only to humans (35,84).…”
mentioning
confidence: 99%